Exploring Evaluation of eHealth Lifestyle Interventions for Preschool Children: A Scoping Review - Marissa C.J. Kooij, MD; Ashley J.P. Smit, MSc; Linda D. Breeman, PhD; Lieke Schiphof-Godart, PhD; Isra Al-Dhahir, MSc; Andrea W.M. Evers, PhD; Koen F.M. Joosten, MD, PhD (Mayo Clinic Proceedings: Digital Health)
EHealth lifestyle interventions can promote positive lifestyle changes in preschool children, but they need to be evaluated to assess their effectiveness and identify areas for improvement. This scoping review aimed to examine evaluation methods, outcome measures, and methodologic strengths and weaknesses, to provide recommendations for the evaluation of eHealth lifestyle interventions for preschool children. A comprehensive literature search was conducted across 6 databases for articles published up to September 29, 2023. We identified 48 articles describing 31 interventions that met our predefined eligibility criteria. These interventions predominantly targeted children’s diet. The most frequently evaluated outcomes were effectiveness, acceptability, and usage. Effectiveness outcomes included, among others, dietary intake, anthropometrics, and child and parental behaviors. Acceptability was evaluated primarily as user satisfaction. Evaluation methods for effectiveness and acceptability included questionnaires, interviews, focus groups, and portable devices. Intervention usage was evaluated via logged use and self-reported data. On the basis of our findings, we present recommendations for future evaluation of eHealth interventions for preschool children. These recommendations focus on selecting relevant outcome measures and appropriate evaluation methods and on integrating and applying evaluation results.